The Role of the Gut-Joint Axis in the Care of Psoriatic Arthritis: A Two-Sample Bidirectional Mendelian Randomization Study - Yihong Gan; Jingqun Liu; Meng Jin; Yilin Zhang; Shuo Huang; Qing Ma; Yanzuo Wu; Li Xu; Jie Bao; Yongsheng Fan (Adis, Springer Healthcare, 2024)
Abstract Introduction Observational studies and clinical trials have supported the association between gut microbiota and psoriatic arthritis. However, the causal link between gut microbiota and psoriatic arthritis is still unclear. Methods A two-sample bi-directional Mendelian randomization analysis was performed using the summary statistics of gut microbiota from the largest available genome-wide association study meta-analysis (n = 13,266) conducted by the MiBioGen consortium. The summary statistics of psoriatic arthritis were extracted directly from the FinnGen consortium, which consists of 3186 psoriatic arthritis patients and 24,086 controls. Sensitivity analyses were conducted to assess the validity of our findings. Enrichment analyses were used to investigate the biofunction and pathways. Results Inverse variance weighted (IVW) estimates suggested that family Rikenellaceae (P = 0.032) and genus Ruminococcaceae UCG011 (P = 0.014) had a detrimental effect on psoriatic arthritis. We also noticed the negative association between the class Methanobacteria (P = 0.032), order Methanobacteriales (P = 0.032), family Methanobacteriaceae (P = 0.032), genus Eubacterium fissicatena group (P = 0.010), genus Methanobrevibacter (P = 0.031), and genus Butyricicoccus (P = 0.041) with psoriatic arthritis. Sensitivity analyses showed that genus Butyricicoccus had pleiotropy and heterogeneity. According to the results of reverse MR analysis, the causal effect of psoriatic arthritis was found on six taxa, respectivelyc family Clostridiaceae1, family Defluviitaleaceae, genus Butyrivibrio, genus Defluviitaleaceae UCG011, genus Clostridium sensu stricto1, and genus Ruminococcaceae UCG011. Conclusion This two-sample bidirectional Mendelian randomization analysis suggested that the gut microbiota had a causal effect on psoriatic arthritis and implied the potential role of probiotics in the management and prevention of psoriatic arthritis.